Science of malaria elimination: using knowledge of bottlenecks and enablers from the Malaria Elimination Demonstration Project in Central India for eliminating malaria in the Asia Pacific region - Rajvanshi, Harsh; Singh, Mrigendra P.; Bharti, Praveen K.; Sahu, Ram Shankar; Jayswar, Himanshu; Govil, Pallavi Jain; Anvikar, Anup; Chan, Xavier Xuanhao; Chebbi, Amita; Das, Sarthak; Lal, Altaf A. (Frontiers in Public Health, 2024)
• Malaria poses a major public health challenge in the Asia Pacific. • Malaria Elimination Demonstration Project was introduced as a public-private partnership initiative in Mandla between State government, ICMR, and FDEC India. • Employed controls for efficient operational and management decisions. • IEC campaigns crucial in schools and communities. • Capacity building of local workers emphasized for better diagnosis and treatment. • SOCH mobile app launched for complete digitalization. • Better supervision for Indoor Residual Sprays and optimized Long Lasting Insecticidal Nets distribution. • Significant malaria cases reduction in Mandla. Published over 20 research papers detailing all aspects. • Insights from MEDP crucial for malaria elimination strategies in other endemic regions of the Asia Pacific.